PENGARUH KINERJA GURU DAN SARANA PRASARANA BELAJAR TERHADAP HASIL BELAJAR SISWA SMP NEGERI SE-KOTA CIREBON - juwita juwita (FKIP Unswagati, 2022)
AbstractThe purposes of the study are to find out: The influence of teachers’ perfomance and learning facilities to the students’ achievement at SMP Negeri Se-Kota Cirebon. The influence of teachers’ perfomance to the students’ achievement at SMP Negeri Se-Kota Cirebon. The influence of learning facilities to the students’ achievement at SMP Negeri Se-Kota Cirebon. The researh uses descriptive corelational method. The population is 99 sosial science teachers at SMP Negeri Se-Kota Cirebon. The results of the research are: There is positive influence of teachers’ perfomance and learning facilities to the students’ achievement at SMP Negeri Se-Kota Cirebon. There is positive influence of teachers’ perfomance to the students’ achievement at SMP Negeri Se-Kota Cirebon. There is positive influence of learning facilities to the students’ achievement at SMP Negeri Se-Kota Cirebon.Keywords: Teachers’ Perfomance, Learning Facilities and the Students’ Achievement